Factors affecting subjective material satisfaction of working women in Peninsular Malaysia - Othman, Mumtazah; Yahaya, Nurizan; Salleh, Naimah; Hashim, Aziah; Sabri, Mohd Fazli (2008)
The ownership of household items is one indication of the high standard of living enjoyed by Malaysian. Previous studies have shown that household items can be used to measure material satisfaction of household (Kleine & Baker, 2004). The objective of this study is to determine factors that influence subjective material satisfaction of working women in Peninsula Malaysia. A total of 418 working women were selected randomly from public and private sectors as well as entrepreneurs. Household items were measured by the ownership of 13 items selected based on the 2000 National Census. Subjective material satisfaction was measured based on level of agreement on ownership of various household appliances. A 4 point Likert scale was utilized based on scores ranging from 1 for strongly disagree, 2 for disagree, 3 for agree and 4 for strongly agree. Sample consisted of women with an average age of 40 years old and a total of 60 % completed high school, 22 % were university graduates and 18 % have diploma/ certificate. Average household income was RM 2030 (USD 580). Compared to the national ownership of household items in the last Census, high acquisition among the respondents is evident with a mean of 10.88 (SD = 2.133) items. Regression analysis showed six predictor variables accounted for 33.8 % of variance in the subjective material satisfaction score (F=8.42, df 5, p=0.000). Importance of household item (β=0.217, p=0.000 ) and household income (β=0.213, p=0.000 ) were significantly related to subjective material satisfaction but not number of household items owned, educational level, and age. In conclusion, the importance of household items makes a better predictor for the subjective material satisfaction of urban working women.